2016
DOI: 10.1037/cdp0000070
|View full text |Cite
|
Sign up to set email alerts
|

Acculturation conflict among Latino youth: Discrimination, ethnic identity, and depressive symptoms.

Abstract: Objectives Patterns of parent-adolescent conflict differ between immigrant and nonimmigrant families living in the United States (Fuligni, 1998). Despite this, there is limited empirical literature examining the nuanced nature of parent-adolescent conflict in immigrant families. To fill this gap, the current study examined the role of two types of conflict (i.e., general and acculturation) in predicting psychosocial outcomes (i.e., depressive symptoms and ethnic identity) among Latino adolescents, and whether … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
51
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(60 citation statements)
references
References 58 publications
4
51
0
2
Order By: Relevance
“…As expected, acculturation conflict was associated with increased risk for being in the psychologically aggressive victims class compared to the uninvolved class among boys (marginal association for girls) although, unexpectedly, this factor did not distinguish the multiform aggressive victims class from either of the other classes. Acculturation conflict and resultant stress may lead to internalizing and externalizing problems that put Latino youth at risk for experiencing and engaging in psychological dating violence (Huq et al 2016; Marsiglia et al 2009; Smokowski, David-Ferdon, et al 2009). Taken together, these findings suggest that parent acculturation and acculturation conflict may be unique sources of risk for Latino youth that should be targeted by Latino dating abuse prevention programs, although more research is needed to understand the mechanisms relating these factors to risk for involvement in different patterns of dating violence.…”
Section: Discussionmentioning
confidence: 99%
“…As expected, acculturation conflict was associated with increased risk for being in the psychologically aggressive victims class compared to the uninvolved class among boys (marginal association for girls) although, unexpectedly, this factor did not distinguish the multiform aggressive victims class from either of the other classes. Acculturation conflict and resultant stress may lead to internalizing and externalizing problems that put Latino youth at risk for experiencing and engaging in psychological dating violence (Huq et al 2016; Marsiglia et al 2009; Smokowski, David-Ferdon, et al 2009). Taken together, these findings suggest that parent acculturation and acculturation conflict may be unique sources of risk for Latino youth that should be targeted by Latino dating abuse prevention programs, although more research is needed to understand the mechanisms relating these factors to risk for involvement in different patterns of dating violence.…”
Section: Discussionmentioning
confidence: 99%
“…In examining these associations, we accounted for the possibility that youth who are immigrants or children of immigrants would experience better psychological adjustment (i.e., fewer symptoms and declining symptomatology over time), based on previous findings in this regard (e.g., Potochnick & Perreira, 2010). Previous research has also shown gender to be a potentially important factor in the prevalence of depression among Latino adolescents (e.g., Huq, Stein, & Gonzalez, 2017); thus, in our analyses, we accounted for the role of gender on initial levels of and change over time in depressive symptoms.…”
Section: Present Studymentioning
confidence: 99%
“…Different contexts exert different demands on ethnic and minority parents that need to be better understood (García Coll & Pachter, ). Prior research discusses the potential impacts of acculturation, or cultural adaptation, on family life (Bostean & Gillespie, ; Huq, Stein, & Gonzalez, ). For instance, greater acculturation among families of Mexican descent has been linked to increased involvement with social support services outside of the home, whereas internal family system values (e.g., cohesion, conflict) remained the same (García Coll & Pachter, ).…”
Section: Discussionmentioning
confidence: 99%
“…However, as children grow older and become exposed to more systems outside of the home, families learn about more dominant cultural values and expectations to which they may feel pressured to adapt (García Coll & Pachter, ). Whereas some traditional parenting practices may be retained in this process (e.g., disciplinary practices), others may be relinquished, which may contribute to confusion, alienation, stress, and family conflict (Bostean & Gillespie, ; García Coll & Pachter, ; Huq et al., ). Thus, findings from this study contribute to this literature by suggesting that frequent family engagement with service systems serving older children may be linked to the “stressor pileup” experienced among minority families associated with the process of cultural adaptation (Murry, Brown, Brody, Cutrona, & Simons, ).…”
Section: Discussionmentioning
confidence: 99%